Coronary Flow. Method of Returning Coronary Bolus - Leguizamón Carlos Alberto; Tenreyro, Elma A.A.; Pecorini, Victorio (Academic Press Inc. (London) Ltd., 1978)
Fil: Leguizamón Carlos Alberto Comisión Nacional de Energía Atómica; Argentina